Coupling relationship of tourism urbanization and rural revitalization: A case study of Zhangjiajie, China. Issue 7 (3rd July 2022) - Ma, Mengyao; Tang, Jianxiong; Dombrosky, James M.
ABSTRACT: This study takes Zhangjiajie, a typical tourist city with abundant tourism resources but economically backward in China, as an example, adding geographic research methods on the basis of traditional coupling research to explore the relationship between the development of tourism urbanization and rural revitalization from 2006 to 2019. The findings revealed the comprehensive index of tourism urbanization grows faster than rural revitalization. Specifically, the level of agglomeration of the tourism industry and the ecological environment had the greatest effect on the coupling system, indicating that they are the critical factors to be considered during macro policy-making.